2012
DOI: 10.1124/dmd.112.048769
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of Gemcitabine Metabolism: Functional Analysis of Genetic Variants in Cytidine Deaminase and Deoxycytidine Kinase

Abstract: Gemcitabine (dFdC, 29, is metabolized by cytidine deaminase (CDA) and deoxycytidine kinase (DCK), but the contribution of genetic variation in these enzymes to the variability in systemic exposure and response observed in cancer patients is unclear. Wild-type enzymes and variants of CDA (Lys27Gln and Ala70Thr) and DCK (Ile24Val, Ala119Gly, and Pro122Ser) were expressed in and purified from Escherichia coli, and enzyme kinetic parameters were estimated for cytarabine (Ara-C), dFdC, and its metabolite 29,29-difl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 15 publications
0
26
1
Order By: Relevance
“…However, a very recent study [36], using purified recombinant proteins instead of the crude cell extracts from transiently overexpressed COS-1 cells used by Gilbert et al [16], reported no differences between the K27 and Q27 recombinant variants in kinetic parameters for ara-C and dFdC. Also, Kirch et al [37] reported a 1.3-to 3.3-fold higher in vitro deamination rate of ara-C for the recombinant K27 variant compared with Q27 variant.…”
Section: Discussionmentioning
confidence: 97%
“…However, a very recent study [36], using purified recombinant proteins instead of the crude cell extracts from transiently overexpressed COS-1 cells used by Gilbert et al [16], reported no differences between the K27 and Q27 recombinant variants in kinetic parameters for ara-C and dFdC. Also, Kirch et al [37] reported a 1.3-to 3.3-fold higher in vitro deamination rate of ara-C for the recombinant K27 variant compared with Q27 variant.…”
Section: Discussionmentioning
confidence: 97%
“…Three SNPs in the CDA-encoding gene, A79C (Lys27Gln), G208A (Ala70Thr), and C435T (Thr145Thr), have been correlated with differential clinical outcomes [14,15,16,17], but the data are inconclusive and conflicting. For example, recombinant enzymes harboring the Gln27 and Thr70 polymorphisms showed reduced activity, with increased K m values for gemcitabine [14,18]. However, the minor allele of this SNP was associated with higher enzymatic activity for gemcitabine in tests performed using lysates of red blood cells taken from Caucasian cancer patients [16,19].…”
Section: Discussionmentioning
confidence: 99%
“…One in vitro study reports that the A allele is associated with decreased CDA enzymatic activity, and a second in vitro study reports that the A allele is associated with decreased CDA activity towards AraC, another deoxycytidine analog, but not towards gemcitabine [26, 36]. Although this variant has not been extensively studied the evidence of an association between it and CDA enzymatic activity is compelling.…”
Section: Cytidine Deaminasementioning
confidence: 99%
“…In vivo studies show an association between decreased DCK protein levels with shorter progression free survival in patients treated with gemcitabine [14, 41, 42]. Despite some well-established correlations between DCK protein levels with resistance to gemcitabine, no SNPs in DCK have shown a consistent association with patient response, or risk of toxicity in clinical studies [21, 22, 26, 43]. The results of those studies are summarized in Table 6.…”
Section: Deoxycytidine Kinasementioning
confidence: 99%